Body mass index and visceral fat: correlation with serum lipid profile in healthy young adults - Moreira, Anabela (2019)
Metabolic and cardiovascular complications and obesity association is well described. Body mass index (BMI) is commonly used to assess obesity, but does not reflect body fat distribution. Abdominal obesity, namely visceral adipose tissue (VAT), is associated with greater risk for those metabolic impairments, including dyslipidemia, than adiposity in other regions of the body. Objective: To determine the correlation between serum lipid profile and anthropometric measures (BMI and VAT) in young healthy adults.